Effect of Fat Extraction Methods on Fatty Acid and Infrared Profiles of Chicken Fat Using GC-MS and FTIR - Aminullah; Mardiah; Hakim, L.; Argani, A.P.; Syahbirin, Gustini (Asian Journal of Chemistry, 2018)
Chicken fat was obtained from rendering and chicken meat processing. The objective of present work was to study fatty acid and infrared characteristics of chicken fat based on several extraction methods. The sample preparation using Soxhlet, Folch, Bligh & Dyer and Hara & Radin methods, analysis of fatty acid using GC-MS and infrared characteristics of chicken fats using FTIR. Analysis of fatty acid showed that both SFA and USFA in Folch were not significantly different with those in Soxhlet and Hara and Radin at 5 % level, however significantly different with those in Bligh and Dyer. In addition, PCA showed fatty acids in Folch can be separated from others. FTIR spectra in general showed no significant differences in C-H stretching at 2922-2852 cm-1, C=O stretching at 1744-1376 cm-1 and the fingerprint absorption at 1000-900 cm-1. In addition, there were two peaks that indicate C-O-C group with force constant of C-O was about 1940 Nm-1.